Phytochemical, cardiovascular effect, antioxidant, anti-inflammation and anti-tumor properties by beta vugaris (beet) root juice. Issue 5 (2019) - Nguyen, H; Nguyen, M; Chandran, V; Nguyen, QH; Nguyen, KT; Nguyen, C
No abstract available